2004
DOI: 10.1111/j.0022-202x.2004.22613.x
|View full text |Cite
|
Sign up to set email alerts
|

GBP-5 Splicing Variants: New Guanylate-Binding Proteins with Tumor-Associated Expression and Antigenicity

Abstract: We have identified a new gene, gbp-5, with high homology to the guanylate binding proteins (GBP) belonging to the GTPase superfamily including the ras gene. gbp-5 is transcribed at least into three splicing variants (gbp-5a, -5b, and -5ta) leading to two different proteins (GBP-5a/b, GBP-5ta). GBP-5ta is C-terminally truncated by 97aa and has therefore lost its isoprenylation site. Although RT-PCR results indicated expression of GBP-5 members in selected normal tissues, western blotting using two newly generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…The only exception is HSD17B1 which has an LTR promoter that appears to contribute placenta-specific expression in addition to normal expression in the ovary (Fournet-Dulguerov et al, 1987;Peltoketo et al, 1999;Sawetawan et al, 1994). We confirmed evidence that the LTR12C (HERV-9) promoter of GBP5 confers an expression pattern in lymphocytes, endothelial cells and a lymphoma cell line that is similar to that of its paralog, GBP1 (Fellenberg et al, 2004;LubesederMartellato et al, 2002;Olszewski et al, 2006;Tripal et al, 2007), data not shown). There is EST evidence that BAAT and MSLN have non-TE alternative promoters as well as their characterized LTR promoters (Kent et al, 2002).…”
Section: Review Of Ltr Exaptationssupporting
confidence: 81%
“…The only exception is HSD17B1 which has an LTR promoter that appears to contribute placenta-specific expression in addition to normal expression in the ovary (Fournet-Dulguerov et al, 1987;Peltoketo et al, 1999;Sawetawan et al, 1994). We confirmed evidence that the LTR12C (HERV-9) promoter of GBP5 confers an expression pattern in lymphocytes, endothelial cells and a lymphoma cell line that is similar to that of its paralog, GBP1 (Fellenberg et al, 2004;LubesederMartellato et al, 2002;Olszewski et al, 2006;Tripal et al, 2007), data not shown). There is EST evidence that BAAT and MSLN have non-TE alternative promoters as well as their characterized LTR promoters (Kent et al, 2002).…”
Section: Review Of Ltr Exaptationssupporting
confidence: 81%
“…SOX9 and the associated miRNA have been implicated in various carcinoma such as colorectal cancer and stand as critical components of regulation of cell cycle, differentiation and development (Jay et al 2005). Transcription factors like GBP have been associated with signalling and proliferation and have been identified as a promising target in cancer therapy (Fellenberg et al 2004;Guimarães et al 2009). Similarly, Lmo-2 expression has been noted to be very high in pancreatic cancer cells and exhibits strong correlation to aggression of prostate cancer and tumour angiogenic conditions (Yamada et al 2002;Ma et al 2007;Nakata et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…6 hGBP-5 has been found at high levels in cutaneous T-cell lymphoma tumor cells. 8 Other members have been identified by bioinformatics search. 5 Among hGBPs, only hGBP-1 and hGBP-2 have been shown to exhibit GTPase activity, and a unique feature of the two proteins is their ability to hydrolyze GTP to a mixture of GDP and GMP.…”
Section: Introductionmentioning
confidence: 99%